Pengaruh Profitabilitas, Busines Risk, Growth of Assets, Operating Leverage terhadap Struktur Modal - Anggraini Oktaviana; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2021)
Business competition today makes many companies strive to achieve their main goals. Maximizing company value is one of the main goals of every company. Maximizing company value by fulfilling company funds that come from internal and external sources of the company. Determination of the proportion of long-term debt and capital in its use as a source of a company has a company that is closely related to the capital structure. This study aims to see the effect of profitability, business risk, asset growth, operating leverage on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This type of research is quantitative. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a sample size of 170 samples using purposive sampling method. The analysis was performed using multiple regression models. The results of this study indicate that: (1) Profitability has a negative and significant effect on capital structure (2). Business risk has a negative and insignificant effect on capital structure (3) Asset growth has a positive and insignificant effect on capital structure (4) Operating leverage has a negative and insignificant effect on capital structure